"Epigenetic" modification as therapy for acute myeloid leukemia. Issue 2 (6th December 2017) - Schiffer, Charles A.
Abstract : The benefits and limitations of the treatment of acute myeloid leukemia/myelodysplasia with epigenetic modifiers are discussed. See also pages 325‐34.